Ear direction is related to jumping success - Merkies, K.; Reid, T.; Seewald, S. (Embracing science to enhance equine welfare and horse-human interactions, 2013)
Hearing in the horse is not only essential to survival as a prey animal, but is also instrumental in understanding the horse for the purposes of training and riding. Ear direction can be a strong indicator of a horse`s response to a task. Ears perked forward normally indicate attentiveness however it could also be a sign of fear in the horse. Ears placed to the side may indicate relaxation or disinterest. Ears turned back may show attentiveness to the rider, while a horse with ears laid back suggests irritation or pain. Little research exists assessing ear direction relating to attention to predict behavioral responses to the rider or environment. This study attempted to correlate ear direction with the success of clearing a jump. Videos of 17 horse-rider combinations were evaluated over 22 jumping efforts in a single Grand Prix class. Ear direction was scored by two independent observers as forward, split (one ear forward, one ear back) or back upon take-off, over and landing after the jump. A mixed model analysis determined that ears positioned either back or split when over or landing after the jump was related to significantly more jumping faults at each obstacle (p<0.001). There was no effect on jumping faults when ears were positioned forward (p>0.05), and ear direction did not appear to have an effect upon take-off for the jump (p>0.05). Thus, ear direction appears to be a predictor of success in clearing a jump. Layperson`s paragraph: Horses that oriented their ears forward while going over a jump are more likely to clear the obstacle successfully than horses who orient their ears back or toward the rider. However ear direction on the approach to the jump does not correlate to jumping success.